Public enemies [videorecording (DVD)] - Mann, Michael, 1943-; Depp, Johnny; Bale, Christian, 1974-; Cotillard, Marion, 1975-; Clarke, Jason, 1969-; Lang, Stephen, 1952-; Wenham, David, 1965-; Dorff, Stephen, 1973-; Ribisi, Giovanni, 1974-; Crudup, Billy, 1968-; Burrough, Bryan, 1961- (Universal Studios Home Entertainment, 2009)
No one could stop Dillinger and his gang. No jail could hold him. His charm and audacious jailbreaks endeared him to almost everyone, from his girlfriend Billie Frechette to an American public who had no sympathy for the banks that had plunged the country into the Depression. But while the adventures of Dillinger's gang thrilled many, Hoover made Dillinger America's first Public Enemy Number One.